2011
DOI: 10.1093/aepp/ppq030
|View full text |Cite
|
Sign up to set email alerts
|

Foregoing Sub‐therapeutic Antibiotics: the Impact on Broiler Grow‐out Operations

Abstract: We use data from a recent national survey to analyze the use of sub‐therapeutic antibiotics (STAs) among broiler growers. We estimate that 42% of growers do not use STAs in their feed or water, and instead rely on a set of other practices, including pathogen testing, expanded sanitary protocols, altered feeding regimens, and Hazard Analysis and Critical Control Point HACCP plans to maintain production. Suspending STAs has no statistically significant impact on production given other inputs, but producers who f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 16 publications
0
24
0
Order By: Relevance
“…After controlling for input levels, operator and farm characteristics, farm production practices, and location, researchers found that AGP use improved output by 1% for feeder-to-finish pig producers, a small and statistically insignificant improvement (Key & McBride 2014). Similar results were found for broilers: Suspending AGPs had no statistically significant effect on production given other inputs (MacDonald & Wang 2011). This study, however, shows large standard errors, with point estimates of 2-7% production declines without AGPs, suggesting a range of outcomes among farms: Some operators can institute substitution practices that compensate for the loss of AGPs, whereas others struggle.…”
Section: Change In Effect Size Over Timementioning
confidence: 69%
See 3 more Smart Citations
“…After controlling for input levels, operator and farm characteristics, farm production practices, and location, researchers found that AGP use improved output by 1% for feeder-to-finish pig producers, a small and statistically insignificant improvement (Key & McBride 2014). Similar results were found for broilers: Suspending AGPs had no statistically significant effect on production given other inputs (MacDonald & Wang 2011). This study, however, shows large standard errors, with point estimates of 2-7% production declines without AGPs, suggesting a range of outcomes among farms: Some operators can institute substitution practices that compensate for the loss of AGPs, whereas others struggle.…”
Section: Change In Effect Size Over Timementioning
confidence: 69%
“…Several major companies (including McDonald's, the fast food chain) have mandated the removal of AGPs from broiler production (MacDonald & Wang 2011). In September 2014, Perdue Foods, the third-largest broiler company in the United States, 1 announced that it had removed all antibiotics from its poultry hatcheries, after phasing out the use of AGPs in its poultry production in 2007 (Perdue Foods 2014).…”
Section: Overview Of Antibiotic Use In Livestockmentioning
confidence: 99%
See 2 more Smart Citations
“…Commercial poultry farmers will have the greatest impact as poultry accounts for 50-75% of total meat production in India 35 . The effects of phasing out of antimicrobials as growth promoters can be limited by replacing less optimized animal production systems with more advanced ones 46,107,108 . The productivity of food animals can be increased by improving nutrition (adding probiotics and feed supplements) and by selecting food animals with superior genetic potential 33 .…”
Section: Reducing and Controlling Antibiotic Use In Animal Productionmentioning
confidence: 99%